2018
DOI: 10.1101/365445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autism-associated Shank3 is essential for homeostatic plasticity and neuronal circuit stability

Abstract: Mutations inShank3 are strongly associated with autism spectrum disorders and 15 circuit disfunction, but a unified view of how Shank3 loss disrupts circuit function and excitability is lacking. Stabilizing, homeostatic forms of synaptic and intrinsic plasticity are critical for preventing circuit hyper-or hypo-excitability, leading us to ask whether Shank3 loss perturbs circuits by disrupting homeostatic plasticity. We show that Shank3 loss abolishes synaptic and intrinsic homeostatic plasticity, which can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Homer1 may drive homeostasis through its interactions with other synaptic proteins in the network that responds to prolonged increases in network activity, including the Shank family of scaffolding proteins. Human SHANK3 is disrupted in an ASD-associated syndrome called Phelan-McDermid Syndrome (Phelan and McDermid, 2012;Wilson et al, 2003) and has been suggested to play a role in homeostatic plasticity in vitro and firing rate recovery in the mouse visual cortex after visual deprivation (Tatavarty et al, 2018). To determine if Shank3, like Homer1, is required for PIN rearrangements observed after whisker trimming, we trimmed the whiskers on one side of Shank3B KO mice (Peça et al, 2011) and measured PiSCES by QMI.…”
Section: Homer1 and Shank3 Are Synaptic Hubs For Homeostatic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Homer1 may drive homeostasis through its interactions with other synaptic proteins in the network that responds to prolonged increases in network activity, including the Shank family of scaffolding proteins. Human SHANK3 is disrupted in an ASD-associated syndrome called Phelan-McDermid Syndrome (Phelan and McDermid, 2012;Wilson et al, 2003) and has been suggested to play a role in homeostatic plasticity in vitro and firing rate recovery in the mouse visual cortex after visual deprivation (Tatavarty et al, 2018). To determine if Shank3, like Homer1, is required for PIN rearrangements observed after whisker trimming, we trimmed the whiskers on one side of Shank3B KO mice (Peça et al, 2011) and measured PiSCES by QMI.…”
Section: Homer1 and Shank3 Are Synaptic Hubs For Homeostatic Plasticitymentioning
confidence: 99%
“…The barrel cortex, which receives tactile input from the whiskers, is a particularly appropriate region to model ASD, given that atypical sensory processing and tactile sensitivity are hallmarks of ASD (Goel and Portera-Cailliau, 2019). Several recent reports have suggested that homeostatic plasticity is altered in some ASD syndromes (Bülow et al, 2019;Tatavarty et al, 2018). Given that E/I imbalance is a mechanism for homeostasis in the barrel cortex, it is especially intriguing that several mouse models of ASD exhibit altered homeostasis in the barrel cortex (Antoine et al, 2019), and that deletion of two different ASD genes in mouse peripheral somatosensory neurons resulted in aberrant tactile sensitivity associated with reduced presynaptic inhibition of primary somatosensory neurons (Orefice et al, 2016).…”
Section: Homeostatic Plasticity and Asdmentioning
confidence: 99%
“…While a reduction in gray matter volume has been found in the cerebellum, hippocampus, amygdala, and parietal lobe of children with autism spectrum disorder (ASD), others have reported an overall increase in brain volume as a hallmark feature of ASD ( Carlisi et al, 2017 ; Riddle et al, 2017 ). Studies on the underlying genes associated with ASD pathogenesis suggest that a range of functions are disrupted such as synaptic maintenance and motor control ( Antoine et al, 2018 ; Golden et al, 2018 ; Tatavarty et al, 2018 ). However, inconsistent structural findings and the seemingly endless number or combination of genetic causes have complicated the process of studying function in autism and other diseases.…”
Section: Main Textmentioning
confidence: 99%
“…An in vivo study has shown that loss of Shank3 led to impairment in the ability of visual cortical circuit recovery following sensory input deprivation [316]. Also, the homeostatic plasticity of neuronal circuits was disrupted in the Shank3 KO model, which hints towards perturbation of the critical period in Shank3 mutation [316].…”
Section: Gene Mutation In Intellectual Disability and Autistic Spectrmentioning
confidence: 99%
“…An in vivo study has shown that loss of Shank3 led to impairment in the ability of visual cortical circuit recovery following sensory input deprivation [316]. Also, the homeostatic plasticity of neuronal circuits was disrupted in the Shank3 KO model, which hints towards perturbation of the critical period in Shank3 mutation [316]. However, using a conditional knockin mouse model, Mei et al [317] showed re-expression of SHANK3 in adulthood restored spine density and synaptic functions in the striatum.…”
Section: Gene Mutation In Intellectual Disability and Autistic Spectrmentioning
confidence: 99%